Penerapan Jaminan pada Bank Syariah dalam Pembiyaan Mudharabah - Wira Purwadi; Agung Subayu Koni; Radjab Djamali (Al-'Aqdu: Journal of Islamic Economics Law, 2022)
The imposition of guarantees carried out by Islamic banks in the practice of mudharabah financing in Indonesia is still a discussion and polemic that has been discussed until now because in sharia implementation the practice of mudharabah financing does not require guarantees, but now Islamic banks apply guarantees in mudharabah financing. In this study using normative juridical research, with an approach to legislation and fatwas from the Indonesian Ulema Council, the purpose of this research is to be able to find solutions to problems regarding the application of guarantees in miudharabah financing in Islamic banks. The results of this study found that the purpose of enactment of guarantees in Islamic banks according to the fatwa is to be able to suppress mudharib to explain their obligations to shaibul maal correctly, also to apply guarantees on the basis of the precautionary principle in Islamic banks in order to minimize risk in the financing, but this is contrary to with sharia principles because mudharaba was born on the basis of profit-sharing cooperation, not debts as in conventional banks. The imposition of guarantees on Islamic banks seems to give the impression of mixing the rules and principles of Islamic banks with conventional banks, this occurs due to the absence of a clear legal basis regarding the imposition of guarantees on mudharabah financing in Islamic banks.